Ömer Nesefî (ö 1142) tefsirindeki soru-cevap üslubu ve bunların tahlili (Fatiha ve Bakara Suresi örneğinde) - Saber, Elsaid Saad Elsaid (My University, 2025)
Kur’an, Allah’ın kelamı ve ilahi kitapların sonuncusu olduğundan herkes onu okumaya, anlamaya ve anlamlandırmaya çalışmıştır. Bu konuda zamanla bu amaca hizmet eden birçok bilim dalı ve farklı yöntemler ortaya çıkmıştır. Tefsir işte bu disiplinlerin birleşimiyle oluşmuştur. Kur’an tefsirleri, ele alınan konu ve ulaşılmak istenen amaçlar açısından kendi aralarında farklılıklar göstermektedir. Örneği, bazı tefsirler ahkam âyetlerini, bazı tefsirler itikad âyetlerini açıklamaya odaklanırken, bazıları Arap dili ve belagatıyla ilgili konulara yoğunlaşmış, bazıları nüzul sebeplerini ve Kur’an kıssalarını açıklamayı amaçlamıştır. Bunlarla birlikte, Ebû Hafs Ömer en-Nesefî’nin et-Teysîr fi’t-Tefsir adlı eseri gibi, bu vb. yönleri bir arada ele alan kapsamlı Kur’an tefsirleri de vardır. Nesefî’nin tefsiri hem yöntemi hem de içeriği açısından önemli ve değerli tefsirlerden biridir. Özellikle Kur’an âyetlerini anlamada geçerli ve etkili bir yöntem olan soru-cevap yöntemini izlemesi bu eserin önemini artıran sebeplerden biridir. et-Teysîr fi’t-Tefsir konulu tez çalışmamız; veri analizi ve tarih araştırması yöntemleri kullanılarak kaleme alınmıştır. Dolayısıyla, Nesefî’nin hayatı, ilmî kişiliği, ilmî yolculukları, hocaları ve ilmî eserleri hakkında bilgiler toplanmış; muhteva ve özellikleri itibarıyla Nesefî tefsiri üzerinde durulmuştur. Ayrıca, rivayet tefsiri ile dirâyet tefsiri arasındaki farklar ve soru-cevap metodu gibi tefsir ilmiyle ilgili bazı ilmî meselelere de değinilmiştir. Araştırmamız esnasında kitap ve makale düzeyinde kaynak bulmakta zorluklar yaşanmıştır. Özellikle, Nesefî’deki bir yorumun farklı yönlerini ele alan kaynaklara ulaşmada zorluk yaşanmışsa da bazı büyük kütüphanelere başvurularak, bazı bilimsel internet sitelerinde araştırma yapılarak ve alanında uzman kişilere danışılarak bu zorluğun üstesinden gelinmeye çalışılmıştır.

Since the Quran is the divine word of Allah and the final revelation among sacred scriptures, its study and interpretation have remained a central scholarly endeavor throughout history. Over time, diverse academic disciplines and methodological frameworks have emerged to facilitate a deeper engagement with its message. Quranic exegesis (tafsir) constitutes a synthesis of these disciplines, bridging linguistic, theological, and jurisprudential analyses. The field of tafsir encompasses a broad spectrum of approaches, each characterized by distinct objectives and methodological orientations. Some exegetes focus on deriving legal rulings (ahkam), while others emphasize theological doctrines (aqida), linguistic intricacies, or rhetorical structures. Additionally, certain exegetical works endeavor to clarify the circumstances of revelation (asbab al-nuzul) and Quranic narratives (qisas). Among the comprehensive exegetical contributions that integrate multiple methodologies into a cohesive framework is Abu Hafs Umar al-Nasafi's al-Taysir fi'l-Tafsir. Nasafi's tafsir represents a significant intellectual achievement in Quranic studies, distinguished by both its methodological rigor and conceptual depth. A defining feature of this work is its structured application of the question-and-answer technique, a pedagogical strategy designed to enhance comprehension and encourage critical engagement with Quranic verses. This dissertation on al-Taysir fi'l-Tafsir employs a combination of historical analysis and data-driven research to examine Nasafi's intellectual legacy. Extensive research has been conducted on his scholarly formation, intellectual influences and exegetical contributions, with particular attention given to the defining features of his tafsir and its methodological framework. Furthermore, critical exegetical debates, including the distinction between narrational (riwayah) and rational (dirayah) exegesis as well as the epistemological implications of the question-and-answer methodology, have been systematically analyzed. The research process has posed significant challenges in sourcing primary and secondary materials, particularly in relation to scholarly assessments of Nasafi's hermeneutical approach. Nevertheless, these obstacles have been methodically addressed through extensive consultation of major academic libraries, utilization of specialized research databases, and engagement with leading scholars in the field.
Keywords: al-Baqara; al-Fatiha; at-Taysir; Commentaries; el-Bakara; el-Fâtiha; et-Teysîr; Kur’an; Mutashabih al-Qur’an; Ömer Nesefî; Question and and Answer; Qur'an; Soru ve cevap; Style; Tafsir; Tefsir; Umar al-Nasafi; Üslüp ve Müteşâbihü’l-Kur’ân